Workplace environment and performance of nurses in a tertiary level hospital (Asian Journal of Medical and Biological Research, 2021)
Workplace environment is an integral part of a hospital. The workplace environment influences on nurses’ performance both positively and negatively. A cross-sectional study was conducted in Chittagong Medical College Hospital, Chittagong from 1st January to 31st December 2017 with the aim to assess the workplace environment and performance of nurses. Total respondents in this study were 210 nurses. Samples were selected by purposive sampling technique. After taking written consent from the respondents, data collection was done by face to face interview using a semi-structured questionnaire with the help of Copenhagen Psychosocial Questionnaire II and Performance Evaluation Rating Scale. Data were analyzed using SPSS. The study findings revealed that 43.3% had good, 51.4% average and 5.2% poor state of physical environment and 10.0% had good, 88.1% average and 1.9% poor state of psychosocial environment. Therefore 70.5% respondents’ performance needed some improvement. The results revealed that there was a significant relationship between educational qualification and workplace performance of nurses (p< 0.001; pulled from χ2 text) and psychosocial environment and workplace performance of nurses (p